Functions of Ornithine Decarboxylase (ODC) in Mouse Ovaries During Development and Reproduction - Lowther, Jenna (Université d'Ottawa / University of Ottawa, 2023)
In 1971 it was discovered by Kobayashi et al that ovarian activity of ornithine decarboxylase (ODC), the rate-limiting step of the polyamine pathway, increased just prior to ovulation in rats. Following the discovery in rats, this phenomenon of ovarian ODC activity increase was seen in several other mammal species, such as mice and pigs. However, despite this discovery occurring fifty years ago the purpose and function of this activity increase are still unknown. One factor of Odc which complicates studies is that whole-body knockouts have been found to be embryonic lethal, with the embryos not making it past embryonic day 3.5. In 2013 our lab found that older mice experienced a smaller ovarian ODC activity increase when compared to their younger counterparts. This decrease in ODC activity corresponded with the increase in reproductive complications typically seen in older mice, such as an increase in miscarriage, and an increased rate of aneuploidies. Furthermore, supplementing the drinking water of these old mice with putrescine, the product of ODC, was found to partially rescue some of these old-age symptoms, such as the rate of miscarriage. In order to further study the purpose of the ovarian ODC rise during the preovulatory period we have generated mice that have had Odc knocked out (Odc-KO) specifically in the oocytes, or in the granulosa cells. Double knockout mice which had Odc knocked out in both the oocytes and granulosa cells were also generated. With these tissue-specific Odc-KO mice, it was hypothesized that a lack of Odc in the oocytes or granulosa cells would negatively impact the follicular development and fertility of the mice. From the oocyte-specific Odc- KO mice we were able to demonstrate that Odc expression in the oocyte is not required for oogenesis. Knocking out Odc in the oocytes was found to have no effect on the development of the oocyte or the surrounding follicle and, no impact was seen on the fertility of the oocyte-specific Odc-KO mice when compared to wild-type controls. The granulosa cell-specific Odc-KO was found to only be a partial knockout. Due to this, the full effects of knocking out Odc in the granulosa cells remain inconclusive. More research is required to find a more reliable method of knocking out genes in the granulosa cells in order to study this further. Additionally, more work on the inhibition of gap junctions to prevent the transmission of polyamines throughout the follicle is required to better understand the effects of Odc expression and polyamines on reproduction.
Keywords: Polyamines; Reproduction; Biochemistry